Spallation of reinforced concrete slabs under contact explosion - Li, J.; Wu, C.; Hao, Hong (2016)
Structures and their occupants are imposed to great threat under blast loading environment. The current design and research practices mainly focus on structural responses and damages under far field or close-in detonations. The blast scenarios involving contact explosions are not extensively investigated. Under contact explosions, highly localized damage caused by severe stress wave propagation is commonly seen, and this damage mode is significantly different from other dynamic loading types in which structural members usually respond in flexural or shear mode. In recent decades, the necessity of gaining in-depth knowledge about this extreme loading event is highlighted as threat from terrorism activities is rising. In the present study, contact test results on reinforced concrete members are presented. Performances of slabs made of normal strength concrete and steel wire mesh reinforced concrete are compared and discussed.